Poor, Rural Women: Spirituality, Religion, and Wellness Across the Life Span. Issue 2 (October 2015) - Gill, Carman Sue; Barrio Minton, Casey; Myers, Jane
<x xml:space="preserve">Abstract</x> Researchers have suggested strategies in the spiritual domain for improving wellness. This study explored relationships among spirituality, religiosity, and wellness for poor, rural women in early adulthood, early–middle adulthood, and middle–later adulthood. Implications for evidence‐based strategies to improve wellness for poor, rural women across the life span are provided.